Ocular cysticercosis: diagnosis and treatment - Sharma, Ananda K (Nepalese Journal of Ophthalmology, 2014)
No Abstract DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11719 Nepal J Ophthalmol 2014; 6(12): 240-241